"I may sound like a native speaker…but I'm not": identities of Korean English teachers with border-crossing experience. Issue 2 (15th March 2021) - Lee, Mun Woo; Kim, Sung Yeon
ABSTRACT: This study examines the identities of Korean English teachers who have lived in various English-speaking countries but now serve as certified public school teachers in Korea. Data were collected from in-depth interviews with seven teachers and analysed via critical discourse analysis. Despite being rated as near-native, the teachers with transnational experience still undervalued their English proficiency, possibly because they compared their proficiency to that of native speakers. They were also found to place emphasis on nativelike pronunciation, particularly American pronunciation. They classified themselves as non-native speakers, stating that they would never be close to native speakers due to innate factors such as nationality or race. The skewed preference towards American English and native speakership was found to be heavily influenced by the socio-cultural ideologies embedded in institutional systems in Korea. These findings reveal the underlying ideologies of English and native speakership in Korea, which highlights the importance of considering teacher's perceptions of their identities in designing teacher training programmes.